The Role of Utility in Investment Patterns: Identifying Dimensions and Its Impact on Financial Decisions - Haji Akbari, Henie; Gholizadeh, Mohammad Hassan; Ebrahimpour Azbari , Mostafa (Business, Marketing, and Finance Open, 2024)
This study analyzes the motivations and factors influencing investors' decision-making in the Iranian capital market, aiming to identify psychological and behavioral patterns affecting financial decisions. Key concepts such as subjective utility, reflecting investors' beliefs and motivations, have been considered in the analysis of financial behaviors. This research demonstrates that psychological, social, and economic factors simultaneously influence investors' attitudes and choices. The ultimate goal of this study is to develop a comprehensive framework to explain the relationship between personality traits, intrinsic motivations, subjective utility perceptions, and investment decision-making processes. Understanding investor behavior is highly important for financial institutions and advisors, as this knowledge can help optimize financial recommendations and provide personalized services. This study adopts a mixed-method approach, including both qualitative and quantitative methods. In the qualitative section, thematic analysis was employed to extract key concepts and gain an in-depth understanding of investors' experiences. Data were collected through in-depth interviews with 20 active investors in the Iranian capital market, selected from various economic and social groups. Theoretical sampling was used as the basis for selecting participants to ensure that individuals with sufficient knowledge and experience participated in the research process. These interviews helped identify investors' subjective values and preferences. In the quantitative section, the Best-Worst Method (BWM) was used to prioritize these values and preferences, enabling precise comparisons between key indicators. Data obtained from pairwise comparisons were processed using statistical analyses to provide reliable scientific results. The study indicates that in addition to financial returns, psychological, social, and economic factors play a central role in shaping investors' preferences. Key motivations include achieving sustainable returns, psychological and financial security, protecting capital against inflation, and the desire to enhance social status. These motivations become even more significant in the context of economic instability and high inflation faced by the Iranian capital market. Additionally, the desire for short-term profits, risk reduction, and diversified portfolio management are other influential factors. Findings show that cognitive biases such as overconfidence and herd behavior can lead to decision-making errors. Moreover, environmental factors such as media influence and social groups also play an important role in financial decisions. The BWM analysis revealed that sustainable returns and psychological security are the top priorities for Iranian investors. The results emphasize that investment decisions are not solely based on economic analyses but are simultaneously influenced by psychological, social, and economic factors. Continuous profitability, capital growth, and maintaining asset value against inflation are the main objectives of investors. Cognitive biases also play a significant role in financial choices. According to BWM analyses, sustainable returns, psychological security, and protection of capital against inflation are the top priorities for Iranian investors, respectively. This study provides a comprehensive insight into investors' behavioral and cognitive preferences, laying the groundwork for designing effective financial policies and tools. Its findings can serve as a basis for developing innovative asset management strategies that not only enhance financial returns but also ensure investors' psychological security. Financial institutions are encouraged to design personalized services based on this study’s findings to meet the specific needs of each investor group. Policymakers should also introduce tools for risk management, reducing cognitive biases, and enhancing information transparency. Further investigation into the role of emerging technologies such as fintech and blockchain can also facilitate fundamental transformations in financial decision-making processes.